V1187 Herculis: A Red Novae progenitor, and the most extreme mass ratio binary known. Issue Volume 14:Issue S346(2019) (August 2018) - Samec, Ronald G.; Chamberlain, Heather; Caton, Daniel; Robb, Russell; Faulkner, Danny R.
Abstract: Complete BVR C I C light curves of V1187 Her were obtained in May 2017 at the Dark Sky Observatory in North Carolina with the 0.81-m reflector of Appalachian State University. Earlier, spectra were taken at the Dominion Astrophysical Observatory with the 1.8-m telescope. The spectral type was found to be F8±1 V (6250 K), so the binary is of solar-type. V1187 Her was previously identified as a low amplitude ( V < 0.2 mag), short period, overcontact eclipsing binary (EW) with a period of 0.310726 d. Strikingly, despite its low amplitude, the early light curves show total eclipses (eclipse duration ≍31.5 minutes), which is a characteristic of an extreme mass ratio binary. A period study covering 11 years reveals a continuous period decrease dP/dt =–4.7×10 –9 d yr –1 . The multi-band Wilson-Devinney light curve solution gives a fill-out of 79% and a mass ratio of only 0.0440±0.0001. There is a cool spot region on the secondary component, which is 400 K hotter than the primary. The inclination is only 66.85±0.05 despite the system's total eclipses.